The effectiveness of emotion-focused couple therapy on positive emotion, marital intimacy and personality abilities of elderly women - Zadhasan , Zohreh; Kazemian moghadam, Kobra (Applied Family Therapy Journal (AFTJ), 2023)
Aim: this study aimed to determine the effectiveness of emotion-focused couple therapy on positive meta-emotion, marital intimacy and personality abilities of elderly women. Methods: The research method was semi-experimental with pre-test-posttest design with control group, and the statistical population of the study was all elderly women referred to counseling centers in Babol in 2021. The sample size consisted of 30 elderly women who were selected by convenience sampling methods according to inclusion and exclusion criteria. The experimental group received couple therapy intervention in 12 sessions of 90 minutes weekly, questionnaires used in this study included positive meta-emotion questionnaire of Mitmansgruber et al.(2009), Thompson and Walker marital intimacy (1993), and personality abilities of Peterson and Seligman (2004). Data were analyzed by repeatedly measuring variance in SPSS software version 22. Results: The results showed that there was a significant difference between the experimental and control groups in terms of positive meta-emotion, marital intimacy and personality abilities (p